Tax Incidence in Heterogeneous Markets: The Pass-through of Air Passenger Taxes on Airfares - Florian Wozny (Institute of Labor Economics (IZA), 2024)
The tax incidence is central to the effectiveness of taxation. In this paper, I examine the pass-through rate of an air passenger tax to airfares. Additionally, I analyse its impact on passenger numbers, air transport capacity, and the interaction with supply and demand elasticity. For identification, I exploit the implementation of an air passenger tax on worldwide departures from Sweden and compare them with similar departures from Denmark and Finland with no such air passenger tax implementation. For the analysis, I use a unique data set of the universe of worldwide airline bookings. On average, airlines choose an immediate and nearly full pass-through of taxes. Consistent with theoretical priors for oligopolistic markets, tax incidence increases with competition but decreases with lower demand elasticity. Furthermore, the air passenger tax reduces passenger numbers and air transport capacity significantly.
Keywords: H22; L13; Q52; 330; tax incidence; competition; air passenger tax; environmental policy